Answer:
Step-by-step explanation:
Key to this method is remembering that
[tex](a+b)^2 = a^2 + 2ab + b^2[/tex]
So, if you divide the coefficient of x by 2 and square it, that will complete the square. With that in mind, things are easy.
6/2 = 3, so add [tex]3^2 = 9[/tex]
[tex]x^2+6x+9 = (x+3)^2[/tex]
So, c=9
Similarly, for the other two,
[tex]c = (\frac{-34}{2} )^2 = (-17)^2 = 289[/tex]
You don't really have to worry about the sign, since squaring will always make it positive
[tex](\frac{25}{13}) ^2 = \frac{625}{169}[/tex]